A review of the genus Carchesiopygus Schedl (Coleoptera: Curculionidae: Platypodinae), with keys to species - Beaver, Roger A.; Sanguansub, Sunisa (Zootaxa, 2015)
The ten species included by Schedl (1972) in the Oriental platypodine genus Carchesiopygus Schedl are reviewed. The genus is rediagnosed and restricted to the following species: Carchesiopygus wollastoni (Chapuis) (type species), C. alternantes Schedl, C. assamensis (Beeson), C. impariporus (Beeson), C. multidentatus (Strohmeyer) and C. oculatus (Beeson), and distinguished from Crossotarsus Chapuis and related genera. The following species are transferred to Platypus Herbst: Carchesiopygus dentipennis Schedl, Carchesiopygus lobacanthus Schedl, Crossotarsus acanthurus Beeson, Crossotarsus psilacanthurus Beeson. Keys are provided to males and females of Carchesiopygus. The taxonomy, distribution and biology of the species are briefly reviewed, and some new records included.